A review of literature and new comprehensive classification of “Mesh Repair Methods” (MRM classification) for abdominal wall hernias - Sortey, Devenndra D. (International Surgery Journal, 2026)
The use of prosthetic mesh has brought a revolution in the history of the repair of abdominal wall hernia. Evidences suggest that using mesh for hernia repair significantly reduces recurrence. Every plane of abdominal musculature has been explored for mesh implantation. Various names have been used to describe each plane and different methods of implantation. But the terminologies used for various practices of mesh implantation are ambiguous and confusing. Inconsistent and confusing terminologies leads to difficulty in comparing and analyzing the literature. The aim of this review is to group various practices by identifying the basic method of utilizing various planes of abdominal wall musculature and bring them under some self-explanatory terminologies. Hernia-mesh implantation methods related articles were searched using Medline, PubMed and the Cochrane library during October 2024 to March 2025. 90 articles were shortlisted for this study. In our review of various available articles, we focused on identifying: abdominal plane utilized, number of planes utilized, number of sheets of mesh implanted, details of mode of implantation (open, endoscopic or hybrid), terminologies used for the planes, and overall name given for that concept. We tried to group various methods of mesh implantation according to above findings. This new comprehensive classification of “mesh repair methods” (MRM classification) is intended to be self-explanatory and its adoption would avoid ambiguity and improve comparison and communications for research studies of various practices of hernia mesh implantation.